Alginate microbeads are coagulation compatible, while alginate microcapsules activate coagulation secondary to complement or directly through FXII. (August 2017) - Gravastrand, Caroline; Hamad, Shamal; Fure, Hilde; Steinkjer, Bjørg; Ryan, Liv; Oberholzer, Josè; Lambris, John D.; Lacík, Igor; Mollnes, Tom Eirik; Espevik, Terje; Brekke, Ole-Lars; Rokstad, Anne Mari
Graphical abstract: Abstract: Alginate microspheres are presently under evaluation for future cell-based therapy. Their ability to induce harmful host reactions needs to be identified for developing the most suitable devices and efficient prevention strategies. We used a lepirudin based human whole blood model to investigate the coagulation potentials of alginate-based microspheres: alginate microbeads (Ca/Ba Beads), alginate poly-l -lysine microcapsules (APA and AP microcapsules) and sodium alginate-sodium cellulose sulfate-poly(methylene-co-cyanoguanidine) microcapsules (PMCG microcapsules). Coagulation activation measured by prothrombin fragments 1 + 2 (PTF1.2) was rapidly and markedly induced by the PMCG microcapsules, delayed and lower induced by the APA and AP microcapsules, and not induced by the Ca/Ba Beads. Monocytes tissue factor (TF) expression was similarly activated by the microcapsules, whereas not by the Ca/Ba Beads. PMCG microcapsules-induced PTF1.2 was abolished by FXII inhibition (corn trypsin inhibitor), thus pointing to activation through the contact pathway. PTF1.2 induced by the AP and APA microcapsules was inhibited by anti-TF antibody, pointing to a TF driven coagulation. The TF induced coagulation was inhibited by the complement inhibitors compstatin (C3 inhibition) and eculizumab (C5 inhibition), revealing a complement-coagulation cross-talk. This is the first study on the coagulation potentials of alginate microspheres, and identifies differences in activation potential, pathways and possible intervention points. Statement of significance: Alginate microcapsules are prospective candidate materials for cell encapsulation therapy. The material surface must be free of host cell adhesion to ensure free diffusion of nutrition and oxygen to the encapsulated cells. Coagulation activation is one gateway to cellular overgrowth through deposition of fibrin. Herein we used a physiologically relevant whole blood model to investigate the coagulation potential of alginate microcapsules and microbeads. The coagulation potentials and the pathways of activation were depending on the surface properties of the materials. Activation of the complement system could also be involved, thus emphasizing a complement-coagulation cross-talk. Our findings points to complement and coagulation inhibition as intervention point for preventing host reactions, and enhance functional cell-encapsulation devices.